Ergonomics program management guidelines for meatpacking plants - USA. Department of Labor. Occupational Safety and Health Administration (Washington, DC, 1993)
These management guidelines are aimed at reducing the incidence and severity of cumulative trauma disorders caused by ergonomic hazards in meatpacking plants. Contents: management commitment and employee involvement; programme elements (worksite analysis, hazard prevention and control, medical management, training and education); detailed guidance and examples for the programme elements. A symptoms survey checklist is included along with a series of questions and answers on the scope of the guidelines, enforcement, compliance, medical management and resources.